Legal implications of changes to State Civil Servants or Aparatur Sipil Negara (ASN) regulations on personnel management systems in Indonesia - Ansori, M. Tedi; Putra, Marta Deki; Triananda, Djorghi Samudra; Iskandar, Iskandar; Madinar, Madinar (Privietlab, 2026)
The amendment of the State Civil Servants or Aparatur Sipil Negara (ASN) regulation through Law Number 20 of 2023 introduced significant normative changes to Indonesia’s personnel management system. This study examines the legal consequences of these regulatory changes from the perspective of state administrative law, focusing on the merit system, institutional oversight, talent management, and the reorganization of non-ASN staff. The methodology utilized in this analysis is normative juridical, employing both statutory and conceptual approaches grounded in secondary legal resources such as statutes, legal theories, academic publications, and formal institutional documents. The findings indicate that Law Number 20 of 2023 enhances the merit system by implementing national talent management and a unified digital system for personnel administration, while offering a more defined legal structure for the reorganization of non-ASN staff. Moreover, the new regulation proposes modifications to the institutional framework governing ASN oversight, including the revision of the supervisory function previously held by the State Civil Service Commission or Komisi Aparatur Sipil Negara (KASN). From an administrative law perspective, these alterations have legal implications for the principles of legality, certainty, accountability, professionalism, and neutrality within public administration. This research contends that while the recent regulation signifies a movement towards modernizing and reinforcing ASN governance, various normative challenges persist, especially in relation to institutional oversight, the harmonization of implementation regulations, and the reliability of merit system protections amid Indonesia's bureaucratic reform initiatives. Consequently, there is a need for comprehensive derivative regulations and enhanced administrative oversight to guarantee legal certainty and the effective execution of the ASN personnel management system.